Simulation of site and topographic effects on ground motion in Los Alamos, NM mesas. Issue 3 (12th December 2019) - Veeraraghavan, Swetha; Coleman, Justin L; Bielak, Jacobo
SUMMARY: Mesas, which consist of an elevated area of land with a flat top and steep cliffs at the sides, are one of the common geological formations present in the Los Alamos region. Previous research has shown that geological formations such as sedimentary canyons can amplify soil response during earthquakes. There have also been parametric studies to understand the response of an idealized and isolated mountain/canyon under inclined plane waves. In this study, a 2-D linear anelastic soil domain, with topography modelled after the Los Alamos region with many mesas and canyons, is considered to understand site-specific topographic effects in the presence of non-isolated topographical features. Various earthquake sources configurations ranging from point sources to finite faults with varying rupture length, dip angles and spatial slip distributions are considered. To isolate the effect of topography, three other soil domains—a homogeneous half-space, homogeneous half-space with mesas and canyons, and a computational domain with just the soil properties from the Los Alamos region on a flat soil domain is also considered. 2-D site-response analyses of these soil domains under earthquake excitation show that the free-field response of the soil can be amplified or de-amplified depending on the topography of the region and the location of the station relative to the fault. These studies also show that even relatively small mesas with height less than 100 m can significantly amplify the response (by a factor of 2 or more), which differ from the much smaller amplification factors (≤1.2) specified by standard building codes such as Eurocode-8 (2000) for topographical features with a similar slope. De-amplifications are also fairly common, especially close to the canyons. The results from this study agree qualitatively with those from the ambient vibration study conducted by Stolte et al. on a mesa from the Los Alamos region. Thus, such site-specific studies provide important insights into the variability of the topographic amplification factors within a region of interest. Such knowledge is important in the design of safety-related critical infrastructure located within that region.